Role Of Lcc Composting To Boost Toxic Substances In Ex-Gold Mining Soil, Kabupaten Sijunjung - Ayu Kurnia Illahi; Dedeh Kurniasih Kurniasih (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
The ex-gold mine area in Kabupaten Sijunjung is experiencing degradation of soil nutrient content, so that the cultivation of agricultural crops does not provide optimal results. One of the steps to improve soil quality is the addition of organic matter. The aim of the study was to obtain compost that has the best nutrient content and is able to bind toxic substances in ex-mining land. The experiment was carried out from June to August 2022 in Kabupaten Sijunjung, Kabupaten Lima Puluh Kota and nutrient content analysis at the Central Plantation Central Laboratory of Pekanbaru Riau. The results of the compost nutrient analysis compared with SNI 7763:2018, showed that the P nutrient content in Mucuna bracteata compost had exceeded the quality standard of solid organic fertilizer. The addition of LCC compost can fix the Al-dd content in the ex-mining soil, from the initial soil test of about 6.40 cmol/kg after incubation with LCC compost, the Al-dd content decreased to <0.10 cmol/kg.